An integrated open-coastal biogeochemistry, ecosystem and biodiversity observatory of the eastern Mediterranean – the Cretan Sea component of the POSEIDON system - George Petihakis; Leonidas Perivoliotis; Gerasimos Korres; Dionysios Ballas; Constantin Frangoulis; Paris Pagonis; Manolis Ntoumas; Manos Pettas; Antonis Chalkiopoulos; Maria Sotiropoulou; Margarita Bekiari; Alkiviadis Kalampokis; et al. (Ocean Science, 2018)
There is a general scarcity of oceanic observations that concurrently examine air–sea interactions, coastal–open-ocean processes and physical–biogeochemical processes, in appropriate spatiotemporal scales and under continuous, long-term data acquisition schemes. In the Mediterranean Sea, the resulting knowledge gaps and observing challenges increase due to its oligotrophic character, especially in the eastern part of the basin. The oligotrophic open Cretan Sea's biogeochemistry is considered to be representative of a greater Mediterranean area up to 106 km2, and understanding its features may be useful on even larger oceanic scales, since the Mediterranean Sea has been considered a miniature model of the global ocean. The spatiotemporal coverage of biogeochemical (BGC) observations in the Cretan Sea has progressively increased over the last decades, especially since the creation of the POSEIDON observing system, which has adopted a multiplatform, multivariable approach, supporting BGC data acquisition. The current POSEIDON system's status includes open and coastal sea fixed platforms, a Ferrybox (FB) system and Bio-Argo autonomous floats that remotely deliver fluorescence as a proxy of chlorophyll-a (Chl-a), O2, pH and pCO2 data, as well as BGC-related physical variables. Since 2010, the list has been further expanded to other BGC (nutrients, vertical particulate matter fluxes), ecosystem and biodiversity (from viruses up to zooplankton) variables, thanks to the addition of sediment traps, frequent research vessel (R/V) visits for seawater–plankton sampling and an acoustic Doppler current profiler (ADCP) delivering information on macrozooplankton–micronekton vertical migration (in the epipelagic to mesopelagic layer). Gliders and drifters are the new (currently under integration to the existing system) platforms, supporting BGC monitoring. Land-based facilities, such as data centres, technical support infrastructure, calibration laboratory and mesocosms, support and give added value to the observatory. The data gathered from these platforms are used to improve the quality of the BGC-ecosystem model predictions, which have recently incorporated atmospheric nutrient deposition processes and assimilation of satellite Chl-a data. Besides addressing open scientific questions at regional and international levels, examples of which are presented, the observatory provides user-oriented services to marine policy makers and the society, and is a technological test bed for new and/or cost-efficient BGC sensor technology and marine equipment. It is part of European and international observing programs, playing a key role in regional data handling and participating in harmonization and best practices procedures. Future expansion plans consider the evolving scientific and society priorities, balanced with sustainable management.